The impact of the Russian-Ukrainian war on the influence of world oil and world gold on the ASEAN-5 Indexes - Iman Lubis Lubis; Arif Surahman; Nani Rusnaeni (Yayasan Pendidikan Penelitian dan Pengabdian Al-amsi, 2023)
In ASEAN are 5 stock markets which have often been studied in previous financial research. The five countries are Indonesia, Malaysia, Philippines, Thailand, Singapore. This research was tested based on the events of the Ukraine-Russia war because this war had the impact of not achieving world economic growth of no greater than 5%.The aim of this research is to examine changes in world oil prices and changes in world gold prices against the ASEAN-5 indexes. Research data comes from investing.com. Variable X1 is changes in world oil prices. Variable X2 is the change in world gold prices. Variable Y is the ASEAN-5 Index. The ASEAN-5 Index countries are Indonesia, the Philippines, Singapore, Malaysia, and Thailand. The data processing technique is panel data. The result is the best random effect. Changes in world oil prices and world gold prices influence changes in the ASEAN-5 Indexes.